(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Acne vulgaris is the most prevalent, accounting for 99% of all cases of acne. The recent advancements exploring the role of CO2 lasers are considered a new shift towards more personalized and effective acne treatment protocols. Objectives: To investigate the satisfaction of patients with acne vulgaris being treated by CO2 laser in combination with Reju White serum at FOB International Cosmetic Dermatological Institute in 2024-2025. Subjects and methods: A cross-sectional descriptive study was performed on 99 patients diagnosed with acne vulgaris and treated at FOB International Cosmetic Dermatological Institute. The clinical manifestations, adverse effects, and treatment outcomes were analyzed. The primary treatment modality was CO2 laser combined with Reju White serum. Results: 67,7% of patients were female, and the most common age group was 20-29 years (47,5%). Oily skin was the predominant skin type (61.6%), and the majority of patients (81.8%) had a disease duration of more than one year. After six weeks of treatment, 86.9% of patients showed good clinical improvement, and 13.1% showed moderate improvement. All patients were satisfied with the treatment; among them, 84.8% were very satisfied. Among the identified factors, treatment outcomes and treatment costs were statistically significant factors influencing patient satisfaction, with a coefficient of determination R² = 0.556 and a significance level of p < 0.05. Conclusion: The combination of CO2 laser and Reju White serum demonstrates good results in treating acne vulgaris, with minimal side effects. The majority of patients expressed high satisfaction with the treatment.